The Neurohermeneutics of Suspicion. A Theoretical Approach (Comparatismi, 2019)
In this paper we argue that Ricoeur’s concept of suspicion is significant for present-day neurocognitive studies on literature, with regard to the issues of embodiment, bodily simulation, and interpretation of textual latent meanings. Ricoeur’s practice of suspicion is one of the two poles of our present inquiry on literary texts, being the second a neurohermeneutic approach that we have developed in past studies (Gambino and Pulvirenti, Storie, menti, mondi; “Neurohermeneutics. A Transdisciplinary Approach to Literature”).We will refer to Ricoeur’s hermeneutics of suspicion, a principle which is often quoted in literary critical discourse but not always precisely defined, considering it as an act of mistrustful interpretation, which bases on intersubjectivity and aims to disclose latent and hidden meanings in sign systems, specifically in literary texts, which is the field of our inquiry.In the perspective of what we here define as neurohermeneutics of suspicion, the reader becomes an interpreter, questioning the text with regard to its multilayered surface features as marking inferential clues unveiling secondary meanings. The meaning-making process depends on a creative act of the reader’s imagination embodying mental (re-)construction of the situation described by a text. Therefore, suspicious interpreting does not rely in either the text, the author, the reader or the cognitive and cultural context, but in their complex and dynamic relationship, pivoting around the common human nature rooted in corporeity. We claim that particularly in the postcritical venture, Ricoeur’s hermeneutics may be helpful in refiguring the pleasure of deciphering the fictional worlds of literature, challenging the reader to “play” with the text intended as a terra incognita of inexhaustible multiple meanings.
Keywords: Neurohermeneutics; Hermeneutics of Suspicion; Embodiment; Situation Models